Fluorodeoxyglucose Positron Emission Tomography integrated with computed tomography in carcinoma of the cervix: Its impact on accurate staging and the predictive role of its metabolic parameters. - Ismaheel O Lawal; Thabo Lengana; Charl Janse van Rensburg; Florette Reyneke; Gbenga O Popoola; Alfred O Ankrah; Mike M Sathekge (PLoS ONE, 2019)
Objectives To determine the impact of FDG-PET/CT in the initial staging of cervical cancer among women with and without HIV and to determine the abilities of FDG-PET/CT metabolic parameters in predicting the presence of distant metastasis. Methods We reviewed the FDG-PET/CT images of women with FIGO stage IB2 to IVA carcinoma of the cervix. We compared the FIGO stage before and after FDG-PET/CT. Maximum and mean standardized uptake values (SUVmax and SUVmean), metabolic tumor volume (MTV) and total lesion glycolysis (TLG) of the primary lesion were determined. We compared these parameters between the HIV-infected and uninfected woman and also determined their abilities to predict the presence of distant metastasis. Results 126 women, mean age 48.05 ± 11.80 years were studied. Seventy-three patients were HIV-infected. The disease was upstaged in 65 patients, 32 of which were upstaged to stage IVB. HIV-infected women were younger (43.36 ± 8.03 years versus 54.51 ± 13.12, p<0.001) and had more advanced disease (p = 0.022) compared with HIV-uninfected. In a univariate logistic regression adjusted for the FIGO stage of the disease, there were significant associations between MTV and TLG of the primary tumor and distant metastasis. SUVmax, SUVmean, MTV and TLG performed well in predicting the presence of distant metastasis with areas under the curves (AUCs) of 0.63, 0.66, 0.80 and 0.77 respectively. These performances improved after adjustment for the FIGO stage of the disease with AUCs of 0.80, 0.79, 0.84 and 0.82 for SUVmax, SUVmean, MTV and TLG respectively. Conclusion Inclusion of 18F-FDG-PET/CT in the pre-therapy assessment of cervical cancer improves the accuracy of staging in about half of the patients. The metabolic parameters of the primary tumor perform well in predicting the presence of distant metastases.